Ethnobotanical study based on the five dimensions of basic life needs in Tidung Tribe of North Kalimantan, Indonesia - Alfi Suciyati; I Gusti Putu Suryadarma; Paidi Paidi; Fadhlan Muchlas Abrori Abrori (Society for Indonesian Biodiversity, 2021)
Abstract. Suciyati A, Suryadarma IGP, Paidi Abrori FM. 2021. Ethnobotanical study based on the five dimensions of basic life needs in Tidung Tribe of North Kalimantan, Indonesia. Biodiversitas 22: 3199-3208. The Tidung tribe is one of the original inhabitants of North Kalimantan, Indonesia. Research results related to the Tidung tribe, especially those related to ethnobotany, are still rare. This research aimed to make an inventory of plant species used by Tidung Tribe based on the five dimensions of basic life needs of Tidung Tribe. The five dimensions of basic life needs of Tidung Tribe is that plants are useful as food (ngakan), shelter (baloy), health/medicine (sihat), traditional ceremony (adat), and clothing (memana). Informants were obtained by conducting snowball sampling consisting of 22 family heads and as many as 65 people. There were three instruments in the data collection: questionnaires of list of plant species, quantitative plant assessment instruments, and semi-structured interviews. According to the inventory result, Tidung Tribe utilize 60 plant species in their daily life. Most of these plants are used as food (ngakan) and traditional medicine (sihat). The Availability Index and Frequency Use Index data showed that Arecaceae, Pandanaceae, Solanaceae, Zingiberaceae, and Poaceae families were the most widely available plants in the research location and most often used by the community.